CREATING ACTIVITIES FOR TEACHING READING TO YOUNG LEARNERS. - Eshniyozova Jasmina Jo’rabekovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This paper provides a comprehensive overview of activities that promote the development of reading skills in young learners. Focusing on interactive and hands-on methods, it suggests various strategies that engage children in the reading process. Through  activities  like  story  mapping,  letter  and  word  hunts,  rhyming  games,  and sequencing,  the  paper  demonstrates  how  educators  can  help  young  students  build essential  skills  such  as  vocabulary  recognition,  comprehension,  and  phonological awareness.  The  study  emphasizes  the  importance  of  repetition  and  visual  support, which  are  key  to  developing  reading  fluency.  It  also  discusses  the  significance  of creating  a  fun  and  stimulating  environment  to  motivate  children  in  their  literacy journey, fostering a love of reading at an early age.